Equilibrium of vegetation and climate at the European rear edge. A reference for climate change planning in mountainous Mediterranean regions. - Ruiz-Labourdette, Diego; Martínez, Felipe; Martín-López, Berta; Montes, Carlos; Pineda, Francisco D (International journal of biometeorology, 2011)
Mediterranean mountains harbour some of Europe's highest floristic richness. This is accounted for largely by the mesoclimatic variety in these areas, along with the co-occurrence of a small area of Eurosiberian, Boreal and Mediterranean species, and those of Tertiary Subtropical origin. Throughout the twenty-first century, we are likely to witness a climate change-related modification of the biogeographic scenario in these mountains, and there is therefore a need for accurate climate regionalisations to serve as a reference of the abundance and distribution of species and communities, particularly those of a relictic nature. This paper presents an objective mapping method focussing on climate regions in a mountain range. The procedure was tested in the Cordillera Central Mountains of the Iberian Peninsula, in the western Mediterranean, one of the ranges occupying the largest area of the Mediterranean Basin. This regionalisation is based upon multivariate analyses and upon detailed cartography employing 27 climatic variables. We used spatial interpolation of data based on geographic information. We detected high climatic diversity in the mountain range studied. We identified 13 climatic regions, all of which form a varying mosaic throughout the annual temperature and rainfall cycle. This heterogeneity results from two geographically opposed gradients. The first one is the Mediterranean-Euro-Siberian variation of the mountain range. The second gradient involves the degree of oceanicity, which is negatively related to distance from the Atlantic Ocean. The existing correlation between the climatic regions detected and the flora existing therein enables the results to be situated within the projected trends of global warming, and their biogeographic and ecological consequences to be analysed.
Keywords: climate; Cordillera Central Mountains of the Iberian Penins; Geographic factors; Global warming; Mediterranean flora; Multivariate regression with climatic data